ONE YEAR RETROSPECTIVE AUDIT OF CNS MALIGNANCY 2 WW REFERRALS. Issue 11 (14th October 2015) - Ashton, Elizabeth; Smeeton, Benjamin; Weatherby, Stuart
Abstract : Background: Since its introduction in 2000, concerns have been raised about the two week wait (2 WW) referral system for suspected malignancy. Studies have demonstrated poor compliance to guidelines, low detection rates and questioned the time effectiveness of the referral process. Method: All patients referred under the 2 WW system for suspected CNS malignancy to Derriford Hospital, Plymouth Hospitals NHS trust, over a one-year period were retrospectively audited. Data was gained from clinic letters and radiological imaging. The aims were to determine the number of referrals, their appropriateness and subsequent time taken to outpatient appointment, imaging and final diagnosis. Results: 103 referrals were made between September 2013 and September 2014 with just 48.5% fulfilling NICE referral guidelines for suspected CNS malignancy. Just three tumours were diagnosed with guidelines identifying all of these. Only 28% of 2 WW referrals received diagnostic imaging and an outpatient appointment within two weeks. Conclusions: Unnecessary referrals are placing strain on the 2 WW system. We suggest that a potential solution is for general practitioners to refer patients for imaging at the same time as they make their neurological 2 WW referral in order to cut down waiting times.